Highly-selective solvent-free catalytic isomerization of α-pinene to camphene over reusable titanate nanotubes. Issue 18 (12th March 2020) - Huang, Geng; Zhou, Shuolin; Liu, Jian; Su, Shengpei; Yin, Dulin
Abstract : Titanate nanotubes prepared by hydrothermal reconstitution and post-modification with HCl aqueous solution were studied in α-pinene isomerization showing high selectivity to camphene. Abstract : Titanate nanotubes, prepared by the hydrothermal reconstitution and modification with hydrochloric acid, were tested as solid acid catalysts in the isomerization of α-pinene under solvent free conditions. The results showed that titanate nanotubes have better catalytic properties than titanium dioxide nanoparticles, and the camphene was the main product for α-pinene isomerization. The effects of several reaction variables, such as reaction temperature, catalyst dosage, and reaction time, on the conversion of α-pinene and the selectivity to camphene were examined. The highest conversion was up to 97.8% with selectivity to camphene of 78.5% under the mild reaction conditions, and the catalyst also showed outstanding reusability after four runs. It is proposed that appropriate surface acidic sites and opened nanotubular structures are mainly responsible for the excellent catalytic performance of titanate nanotubes materials.